2016
DOI: 10.1242/jeb.138396
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in gastrointestinal morphology and enzyme activity in lactating striped hamsters (Cricetulus barabensis)

Abstract: In small mammals, marked phenotypic plasticity of digestive physiology has been shown to make it easier for them to cope with energetically stressful periods, such as lactation. It has been proposed that the capacity of the gut to digest and absorb food is not the limiting factor to sustained energy intake (SusEI) during peak lactation. In this study, plasticity in energy intake and gastrointestinal morphology was examined in striped hamsters at different stages of reproduction and when raising litters of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Much research on dietary plasticity has focused on aminopeptidase (e.g. Sabat et al, 1999;Naya et al, 2008a;Zhang et al, 2016), a protein-digesting enzyme found throughout the small intestine (Miura et al, 1983;Naya et al, 2008a). Our finding that protein deficiency localizes morphological flexibility to the proximal small intestine suggests that enterokinase, an enzyme expressed at highest levels in the most proximal part of the duodenum (Nordström and Dahlqvist, 1971;Yuan et al, 1998), may be an important actor in dietary flexibility.…”
Section: Enterocyte Morphologymentioning
confidence: 85%
“…Much research on dietary plasticity has focused on aminopeptidase (e.g. Sabat et al, 1999;Naya et al, 2008a;Zhang et al, 2016), a protein-digesting enzyme found throughout the small intestine (Miura et al, 1983;Naya et al, 2008a). Our finding that protein deficiency localizes morphological flexibility to the proximal small intestine suggests that enterokinase, an enzyme expressed at highest levels in the most proximal part of the duodenum (Nordström and Dahlqvist, 1971;Yuan et al, 1998), may be an important actor in dietary flexibility.…”
Section: Enterocyte Morphologymentioning
confidence: 85%
“…For example, in striped hamsters ( Cricetulus brabensis ), these changes are correlated with changes in food intake, digestive efficiency and gene expression of AgRP in the hypothalamus . However, in this situation, the levels of POMC and CART were unchanged despite the large differences in food intake, and trends in both NPY and leptin levels were not significant . Given the trends, however, this could be a power issue at the low sample size.…”
Section: Regulation Of Intestinal Growth During Endogenous Energy Defmentioning
confidence: 99%
“…This energetic challenge provides further insight into the link between adipose tissue‐associated energy loss and intestinal growth. Notably, lactation involves large increases in energy intake and intestinal growth on a background of reduced adipose tissue mass and lowered leptin levels . At the hypothalamic level, lactation reduces the expression of POMC and increases the expression of AgRP and NPY in the ARC and increases the expression of NPY in the dorsomedial hypothalamus .…”
Section: Regulation Of Intestinal Growth During Endogenous Energy Defmentioning
confidence: 99%
See 2 more Smart Citations